Sociocultural adjustment of international students in higher education: A case study of Yemeni postgraduate students. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2012)
This article presents the findings of a study that examined the sociocultural adjustment of Yemeni postgraduate students in a public university in Malaysia. Data collection included a questionnaire, journal writings and focus group interviews. The analysis of data revealed that the sociocultural adjustment difficulties faced by Yemeni postgraduate students in the public university include among others, making friends, getting used to the local food, understanding cultural differences, understanding the local accent/language and dealing with people in authority. To overcome such sociocultural difficulties, the Yemeni postgraduate students either remained passive or adapted themselves to the norms of the new environment. The findings reveal that these specific sociocultural difficulties faced by the Yemeni postgraduate students should be handled carefully by university administrators to allow the postgraduates to experience a more positive academic student experience. The findings reported contribute to the ongoing interest of research into the experience of international students in the Malaysian landscape of higher education as well as in other higher education contexts.